Teologi Kama: Deva, Poros Kehidupan, dan Kenikmatan - I Gede Suwantana (Sphatika: Jurnal Teologi, 2021)
Kama is an eternal human matter. Every civilization traces it deeply. India in the context of Hindu civilization is one that is very massive in discussing it and it is stated in both literary works and reliefs of sacred buildings. The discussion not only concerns about sexual relations and their behavior, but tries to explore the secret spaces that are in it. When the existence of the kama leaves a side of the secret that is not able to be revealed, then appear the form of the Kama God who represents kama itself, so that the human mind is able to reach it. This work descriptively describes aspects of the theology of kama extracted from text sources. In the divinity map, Kama is a God or is called a Kama God. Then, the Siva-Parvati, Rama-Sita, and Radha-Krishna relations formed a cluster of theologies which were the object of worship in the religious life of the Hindu community. In the reality of life, kama is associated with the art of making love and important actions in terms of regeneration for the continuity of life.